Evidence for poplar PtaPLATZ18 in the regulation of plant growth and vascular tissues development - Guérin, Claire; Behr, Marc; Sait, Julie; Mol, Adeline; El Jaziri, Mondher; Baucher, Marie (Frontiers in Plant Science, 2023)
Plant A/T-rich protein and zinc-binding protein (PLATZ) are plant-specific transcription factors playing a role in plant development and stress response. Here we report the identification of PtaPLATZ18, a poplar gene preferentially expressed within developing xylem, and the impact of its dominant repression on plant development. Poplar dominant repressor lines for PtaPLATZ18, produced by overexpressing a PtaPLATZ18-SRDX fusion, showed increased plant height resulting from higher internode length. Stem undergoing secondary growth phase of PtaPLATZ18-SRDX lines were characterized by an enhanced xylem production and lignin content compared to the wild type. This latter phenotype was linked to an increased expression of genes involved in lignin biosynthesis and polymerization. The phenotype observed in the PtaPLATZ18-SRDX lines argues that this transcription factor targets key regulators of plant growth and development with effects at morphological, anatomical, and biochemical levels.